Hack work. (Economist, 2016)
The article discusses the impact of hacking on the insurance industry. Topics discussed include the offering of cyber-insurance policies against data breaches, insurers' coverage of only the direct costs that a company incurs from a hack and the European Union (EU) data-protection rules which will impose stricter notification requirements and stiffer fines for data breaches.